Socio-Economic Changes in Uzbekistan during the Years of Independence - Ziyaev Farkhod Sobirovich (International Journal on Integrated Education, 2024)
This article discusses the economic issues of foreign relations on the example of Surkhandarya, the southern region of Uzbekistan, and the expansion of development ties with the impact of New Uzbekistan on the Surkhandarya oasis. During the years of independence, Surkhandarya has a special place in the economic relations of the country. The region has an abundance of raw materials and borders with Afghanistan.